CSF Biomarkers of Alzheimer Disease in Patients With Concomitant α-Synuclein Pathology. (15th November 2022) - Cousins, Katheryn Alexandra Quilico; Arezoumandan, Sanaz; Shellikeri, Sanjana; Ohm, Daniel; Shaw, Leslie M.; Grossman, Murray; Wolk, David; McMillan, Corey T.; Chen-Plotkin, Alice; Lee, Edward; Trojanowski, John Q.; Zetterberg, Henrik; et al.
Abstract : Background and Objectives: CSF biomarkers β‐amyloid 1-42 (Aβ42 ), phosphorylated tau 181 (p-tau181 ), total tau (t-tau), and neurogranin (Ng) can diagnose Alzheimer disease (AD) in life. However, it is unknown whether CSF concentrations, and thus their accuracies, are affected by concomitant pathologies common in AD, such as α-synuclein (αSyn). Our primary goal was to test whether biomarkers in patients with AD are altered by concomitant αSyn. We compared CSF Aβ42, p-tau181, t-tau, and Ng levels across autopsy-confirmed AD and concomitant AD and αSyn (AD + αSyn). Antemortem CSF levels were related to postmortem accumulations of αSyn. Finally, we tested how concommitant AD + αSyn affected the diagnostic accuracy of 2 CSF-based strategies: the amyloid/tau/neurodegeneration (ATN) framework and the t-tau/Aβ42 ratio. Methods: Inclusion criteria were neuropathologic diagnoses of AD, mixed AD + αSyn, and αSyn. A convenience sample of nonimpaired controls was selected with available CSF and a Mini-Mental State Examination (MMSE) ≥ 27. αSyn without AD and controls were included as reference groups. Analyses of covariance (ANCOVAs) tested planned comparisons were CSF Aβ42, p-tau181, t-tau, and Ng differences across AD and AD + αSyn. Linear models tested how biomarkers were altered by αSyn accumulation in AD, accounting for pathologic β-amyloid and tau. Receiver operating characteristic and area under the curve (AUC), including 95% CI, evaluated diagnostic accuracy. Results: Participants were 61 patients with AD, 39 patients with mixed AD + αSyn, 20 patients with αSyn, and 61 controls. AD had similar median age (73 [interquartile range IQR = 12] years), MMSE (23 [IQR = 9]), and sex distribution (male = 49%) compared with AD + αSyn age (70 [IQR = 13] years; p = 0.3), MMSE (25 [IQR = 9.5]; p = 0.19), and sex distribution (male = 69%; p = 0.077). ANCOVAs showed that AD + αSyn had lower p-tau181 (F(1, 94) = 17, p < 2.6e-16), t-tau (F(1, 93) = 11, p = 0.0004), and Ng levels (F(1, 50) = 12, p = 0.0004) than AD; there was no difference in Aβ42 ( p = 0.44). Models showed increasing αSyn related to lower p-tau181 (β = −0.26, SE = 0.092, p = 0.0065), t-tau (β = −0.19, SE = 0.092, p = 0.041), and Ng levels (β = −0.2, SE = 0.066, p = 0.0046); αSyn was not a significant factor for Aβ42 ( p = 1). T-tau/Aβ42 had the highest accuracy when detecting AD, including mixed AD + αSyn cases (AUC = 0.95; CI 0.92–0.98). Discussion: Findings demonstrate that concomitant αSyn pathology in AD is associated with lower CSF p-tau181, t-tau, and Ng levels and can affect diagnostic accuracy in patients with AD.